2018
DOI: 10.1111/jtxs.12365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and heating conditions on the properties of Alaska pollock (Theragra chalcogramma) surimi gel fortified with fish oil

Abstract: To improve the quality and functionality of emulsified surimi gels, the effect of pH and heating conditions on the properties of surimi gel fortified with fish oil was investigated. Results showed that pH conditions influenced the solubility and emulsifying properties of surimi proteins and that the gel properties were associated with the protein properties. Under direct heating, the highest gel strength was achieved at pH 8.0, in which condition the solubility was significantly higher than others. Higher emul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The solubility of squid protein was determined according to the method described by Gao [ 14 ], with slight modifications. Approximately 1 g of squid muscle was homogenized with 20 mL of 0.6 M salt solution by a homogenizer (T18 digital, IKA Group, Staufen, Germany) at 10,000 rpm for 30 s. The mixture was then centrifuged at 13,000× g (Multifuge X1R, Thermo Fisher Scientific Co., Ltd., Shanghai, China) at 4 °C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The solubility of squid protein was determined according to the method described by Gao [ 14 ], with slight modifications. Approximately 1 g of squid muscle was homogenized with 20 mL of 0.6 M salt solution by a homogenizer (T18 digital, IKA Group, Staufen, Germany) at 10,000 rpm for 30 s. The mixture was then centrifuged at 13,000× g (Multifuge X1R, Thermo Fisher Scientific Co., Ltd., Shanghai, China) at 4 °C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Protein solubility was determined according to the method described by Gao et al (2018) with some modifications. Squid meat (1 g) was homogenized with 10 ml of different salt solutions.…”
Section: Determination Of Protein Solubilitymentioning
confidence: 99%
“…Li, 2020). Then, G' and G 00 began to decline due to endogenous protease activity, which led to the degradation of the gel network structure (Gao et al, 2018). Finally, G' and G 00 continued to increase with increasing temperature above 60 C. The addition of SC and ST induced different trends in G' and G 00 .…”
Section: Color Analysismentioning
confidence: 99%
“…Notably, the addition of polyunsaturated fatty acids (PUFAs) not only improves the healthy functionality but also the properties of MP gels (Z. Han et al., 2021). For example, some reports have concluded that the introduction of fish oil improved the gelation performance, WHC, and whiteness of surimi‐based products (Gao et al., 2018; Jiao et al., 2019; Yu and So et al., 2022). Moreover, the contributions of PUFAs to gel properties may depend on the oil types and levels.…”
Section: Benefitsmentioning
confidence: 99%
“…Difference in the response of actomyosin to pH may be ascribed to their distinct amino acid compositions. Gao et al (2018) found that pH influenced the solubility and emulsifying attributes of surimi proteins and the subsequent gel properties. A greater gel strength was obtained at pH 8-8.5, where the surimi gel also showed the highest emulsifying stability.…”
Section: Phmentioning
confidence: 99%